"We Don't Belong There": New Geographies of Homelessness, Addiction, and Social Control in Vancouver's Inner City. (29th August 2018) - Fast, Danya; Cunningham, David
Abstract: Drawing on eight years of ethnographic research in Vancouver's inner city, we explore how aligned processes of gentrification and poverty management are producing new geographies of homelessness, addiction, and social control for young people who use drugs and inhabit the social, spatial, and economic margins of urban space. In particular, we examine the emergence of government‐subsidized supportive housing for youth in this setting. Tracing the experiences of a small number of individuals across time, we show how this contemporary mode of urban governance is producing new forms of life and senses of place for young people in the margins, including new kinds of embodied displacement and disappearance in the city. [Youth; Addiction; Homelessness; Housing; Gentrification; Poverty Management; Lines of Flight]